Using paleometry to address biogenicity in paleobiology - Saldanha, João Pedro; Martins, Alisson Klayton; Osés, Gabriel Ladeira; Callefo, Flavia (Frontiers in Ecology and Evolution, 2025)
Biogenicity assessments in paleobiology encompass a broad range of criteria, arguments, and methodological approaches for evaluating the origin of fossil objects and purported biological materials. Amid this uncertainty, paleometry emerges as a critical tool for deepening and refining our understanding of biogenicity. This study aims to systematize procedures observed across recurring patterns in the literature, to critically examine the type of data acquired, and to expand the application of high-resolution analytical techniques. Rather than debating optimal criteria, we propose a direct and structured framework for biogenicity assessment, outlining standardized steps, choosing the most powerful techniques for solving specific issues, result interpretation, and scientific discussion. Biogenicity-related studies are categorized into three major groups: (1) dubiofossils, including microfossil-, ichnofossil-, and biomineral-like forms; (2) fossilization processes involving microbial mediation; and (3) potential biominerals associated with skeletal metazoans. Despite their differences, these categories share a fundamental reliance on reconstructing diagenetic history, a prerequisite for any meaningful biogenicity inference. In this context, paleometry plays a central role across all stages of investigation. Our analysis highlights the widespread use of high-resolution, non-destructive techniques such as optical microscopy (OM), scanning electron microscopy with energy-dispersive spectroscopy (SEM-EDS), micro-Raman spectroscopy (µ-RS), and Fourier-transform infrared spectroscopy (FT-IR), largely applied for their minimal sample preparation and versatile micrometer-scale capabilities. We also propose the utilization of other techniques, still underexplored in biogenicity studies. Furthermore, the temporal distribution of case studies reveals a concentration of research on geologic intervals associated with key evolutionary and environmental transitions, which we argue the distribution of biogenicity studies in such periods. The protocols proposed herein offer a flexible and reproducible methodological pathway. By guiding researchers from analytical technique selection to data interpretation, this framework aims to facilitate future investigations and foster more coherent discussions around the biogenicity of paleobiological materials.